QUALITY OF BASIC, TERTIARY EDUCATION AND ADULT LEARNING IN THE EUROPEAN UNION: THE KEY TRENDS - Cichoracki, Michał (The Modern Higher Education Review, 2021)
The quality of education and training is considered in the European Union (EU) as a subject of the highest political priority. In all member states high levels of professional skills, social competencies and knowledge are considered to be the very basic conditions for active citizenship, social cohesion and employment. High quality of education and lifelong learning are the most important means of shaping one’s future on a professional and personal level – they are essential in the light of labour market strategies, and the free movement of workers within the European Union. The EU has already achieved one of its six 2019/2020 benchmarks for education and training and is close to meeting three others. The target of raising the share of the population aged 30 to 34 that has completed tertiary or equivalent education to at least 40 % was met in 2019. In addition, the EU is well on track to meeting its 2019/2020 benchmarks for early leavers from education and training and for early childhood education and care. The share of employed recent graduates has also increased over the past five years. However, the situation is less favourable as regards the remaining two others benchmarks: education outcomes – as measured by pupil’s performance in the Programme for International Student Assessment (PISA) study for reading, maths and science – are moving away from the respective EU target. Moreover, due to the stagnation in the proportion of adults participating in the learning process, the benchmark of raising this share to 15 % in the years to come will likely be missed.